2007
DOI: 10.1111/j.1471-4159.2007.04566.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals altered cholesterol metabolism during the neurodegeneration in mouse scrapie model

Abstract: To identify the dynamic transcriptional alterations in CNS during the development of prion disease, brains of scrapieinfected mice and age-matched, mock-inoculated controls were analyzed immediately before inoculation and at different time points post-inoculation using Affymetrix microarray technique. A total of 449 probe sets, representing 430 genes, showed differential expression between scrapie-and mockinoculated mice over the time course. These genes could be separated into two clusters according to expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
2
28
0
2
Order By: Relevance
“…Furthermore, in a recent systems biology study based on gene expression changes in mice with scrapie, mRNA levels of C1qa/b and C3ar1 reflecting activation of microglia and astrocytes are among the first detectable expression changes (10 weeks postinfection) and precede, e.g., clinical signs by many weeks (16). Not only are our results consistent with early changes of gene expression in mice infected with the TSE agent (16,36), they are also consistent with the behavioral changes in the early stages of prion infection in mice (9,10,20). Prion-infected mice have shown significant inability to discriminate a novel object from 7 week postinoculation compared with healthy mice (20).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, in a recent systems biology study based on gene expression changes in mice with scrapie, mRNA levels of C1qa/b and C3ar1 reflecting activation of microglia and astrocytes are among the first detectable expression changes (10 weeks postinfection) and precede, e.g., clinical signs by many weeks (16). Not only are our results consistent with early changes of gene expression in mice infected with the TSE agent (16,36), they are also consistent with the behavioral changes in the early stages of prion infection in mice (9,10,20). Prion-infected mice have shown significant inability to discriminate a novel object from 7 week postinoculation compared with healthy mice (20).…”
Section: Discussionsupporting
confidence: 87%
“…At 36 mpi, the expression of NR1H3 reached its lowest level (Ϫ4.7-fold of the negative controls). This might be linked to the downregulation of cholesterol synthesis similar to the findings in mice with scrapie (36). The nuclear oxysterol receptors liver X receptor-alpha [LXRalpha (NR1H3)] and LXRbeta (NR1H2) regulate genes involved in cholesterol homeostasis in a coordinate manner.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Because blocking the function of DRMs by reducing the levels of cholesterol or sphingomyelin in cultured neurons is known to induce the formation of varicosities and the elimination of synaptic spines (Hering et al, 2003), it may be tempting to speculate that the occurrence of varicosities in scrapie may be related to the accumulation of PrP Sc in DRMs. In support of this hypothesis, cDNA microarray studies identified several differentially expressed genes related to cholesterol synthesis during the presymptomatic phase of prion disease (Xiang et al, 2007;Skinner et al, 2006). Additional studies will have to prove whether alterations in the cholesterol synthesis or DRM function, because of PrP Sc accumulation, represents the primary cause of varicosity emergence and subsequent spine loss in prion disease.…”
Section: Preferential Loss Of Persistent Spinesmentioning
confidence: 95%